Pandora hearts. 15 - Mochizuki, Jun (Yen Press, 2013)
"Brother, master, friend. There once was an impure soul who, unknowingly, sealed a contract with Humpty Dumpty in the dark bowels of Sablier. But the time has come for him to face both his true self and his sins. Reexamining the events that have led him to this juncture, he comes to a realization and, choosing to stand by his convictions, decides on a course of action-- as though it may yet save him somehow" -- from publisher's web site.